PENGARUH JUS BUAH NAGA MERAH TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETES MILETUS TIPE 2 DI WILAYAH KERJA PUSKESMAS MELUR KECAMATAN SUKAJADI KOTA PEKANBARU - Riamah Riamah; Nadia Fitriani Ritonga (Ensiklopedia of Journal, 2022)
Diabetes melitus (DM) a disease characterized by hyperglycemia and disturbances of carbohydrate, lipid, and protein metabolism associated with absolute or relative deficiency of insulin action and/or secretion. Red Pitaya Fruit can be used as a balancer of glucose levels because it contains a variety of 2 kinds of antioxidant that is vitamin C, betakaroten dan flavonoid (quercetin, kaempferol, and isoramnetin). The purpose of this research is to find out The Effect of Red Pitaya Fruit Juice on Reducing glucose Levels in Type 2 Diabetes Mellitus in the Melur Public Health Center Melur, Sukajadi, Pekanbaru City. Research design with quasi-experimental. This research was conducted from Maret-July 2021, population of 482 people, sample of 30 people, intervention group of 15 people, control group of 15 people. Intervention group gets Red Pitaya Fruit juice in the afternoon regularly for 1 week and control group was given an examination on the first and last day. The measuring instrument was Autocheck GCU 3in1. Data Analysis used dependent sample T-test test on the intervention group p value 0,000 (< 0,05) while the control group p value 0,068 (> 0,05). It can be concluded that there are differences in glucose levels in patients with diabetes mellitus who are given red pitaya fruit juice with those not given. It hoped that an alternative way to lower glucose on people with diabetes mellitus can consume red pitaya fruit juice.Keywords: Diabetes Mellitus, Glucose Levels, Red Pitaya Fruit Juice